2017
DOI: 10.1016/s1470-2045(17)30243-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel molecular subgroups for clinical classification and outcome prediction in childhood medulloblastoma: a cohort study

Abstract: SummaryBackgroundInternational consensus recognises four medulloblastoma molecular subgroups: WNT (MBWNT), SHH (MBSHH), group 3 (MBGrp3), and group 4 (MBGrp4), each defined by their characteristic genome-wide transcriptomic and DNA methylomic profiles. These subgroups have distinct clinicopathological and molecular features, and underpin current disease subclassification and initial subgroup-directed therapies that are underway in clinical trials. However, substantial biological heterogeneity and differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
531
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 431 publications
(562 citation statements)
references
References 28 publications
16
531
0
15
Order By: Relevance
“…Surprisingly, although Group 3 MBs are often generalized as a subgroup defined by aberrant MYC expression across the subgroup (Roussel and Robinson, 2013), we observed an inverse correlation between the photoreceptor program defined by NRL/CRX activity and gene sets associated with MYC family amplification. This observation is consistent with the concept of intra-subgroup heterogeneity in MB (Cavalli et al, 2017; Northcott et al, 2017; Schwalbe et al, 2017) and thus, our data further support that Group 3 MBs are comprised of molecularly and phenotypically distinct subtypes. Importantly, we showed that NRL/CRX are not only responsible for regulating the photoreceptor program in Group 3, but are also required for maintenance of the malignant phenotype of these tumors.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Surprisingly, although Group 3 MBs are often generalized as a subgroup defined by aberrant MYC expression across the subgroup (Roussel and Robinson, 2013), we observed an inverse correlation between the photoreceptor program defined by NRL/CRX activity and gene sets associated with MYC family amplification. This observation is consistent with the concept of intra-subgroup heterogeneity in MB (Cavalli et al, 2017; Northcott et al, 2017; Schwalbe et al, 2017) and thus, our data further support that Group 3 MBs are comprised of molecularly and phenotypically distinct subtypes. Importantly, we showed that NRL/CRX are not only responsible for regulating the photoreceptor program in Group 3, but are also required for maintenance of the malignant phenotype of these tumors.…”
Section: Discussionsupporting
confidence: 92%
“…This recognized overlap may explain why a small fraction of Group 4 MBs exhibit high levels of NRL / CRX . The recent demonstration of intragroup heterogeneity (Cavalli et al, 2017; Northcott et al, 2017; Schwalbe et al, 2017) further contextualizes these observations, as we noted high NRL/CRX expression mainly in pure Group 3 subtypes (namely subtypes II and III) and to a lesser extent in mixed subtypes (namely NRL in subtype I). shRNA-mediated perturbation of NRL and subsequent transcriptional analysis of targeted cells validated the computational inferences we derived from primary enhancer/transcriptome datasets, confirming that NRL controls the photoreceptor program and a subset of Group 3 signature genes.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Neben den klassischen histologischen Kategorien führte die molekulargenetische Charakterisierung von Medulloblastomen zur Definition von vier distinkten Subgruppen [33,34], die in Zukunft weitere Differenzierungen erfahren werden [35][36][37]. Ziel dieser Klassifizierungen ist die Verbesserung der risikoadaptierten Therapie, das heißt die Steigerung der Heilungsrate bei Minimierung unerwünschter therapieassoziierter Langzeitfolgen (zum Beispiel intellektuelle und neuroendokrine Beeinträchtigun-gen) sowie die Identifikation aberranter Signaltransduktionswege als Angriffspunkt zielgerichteter Therapieansätze [33].…”
Section: Klinische Charakteristikaunclassified
“…Das Gorlin-Syndrom (Basalzellnävus-Syndrom, Gorlin-Goltz-Syndrom, nävoi-des Basalzellkarzinom-Syndrom) ist durch multiple Basalzellkarzinome vor dem 30 [35].…”
Section: Genetische Dispositionunclassified